Development of A Real‐Time PCR Assay for the Detection of Trichinella Spiralis in Muscle Tissue of Swine and Derivatives. Issue 2 (11th December 2015) - Quintana, S.; Recavarren, M.; Scialfa, E.; Viera, I.; Rivero, M.; Krivokapich, S.
Abstract: Trichinellosis is an emergent zoonosis in several regions of the world and it is considered a public health problem. Trichinellosis represent one of the most important zoonotic diseases in Argentina. The purpose of this study was to develop a real‐time PCR assay with internal control to detect Trichinella spiralis DNA in samples of swine muscles and its derivatives. PCR amplification of DNA from muscle samples was performed by real‐time PCR with an internal porcine DNA amplification control. The developed PCR assay specifically detects T. spiralis showing no amplification with other Trichinella genotypes and showed an estimated sensitivity of 0.024 larvae per gram in swine muscle samples. From the 21 samples analyzed, five samples negative by enzymatic digestion were positive by real‐time PCR, which demonstrates that this technique is capable of detecting T. spiralis in cases when enzymatic digestion cannot. In this work, a new molecular assay with internal control for T. spiralis detection was successfully developed. Practical Applications: Trichinellosis is considered a public health problem in Argentina and also represents an economic problem in porcine animal production and food safety. Due to the predominantly zoonotic importance of infection, the main efforts have focused on the control of Trichinella or the elimination of Trichinella from the food chain. In our country, most human infections are caused by Trichinella spiralis, which is transmitted mainly by the ingestion of raw or undercooked infected swine meat or its derivative products. New controls in order to improve food safety for consumers should be developed. This new real‐time PCR assay with internal control shows a substantial increase in diagnostic sensitivity in comparison with muscle artificial digestion and the possibility to avoid false negative results. This specific PCR for T. spiralis may be useful for detection of infection at early stages in humans and food animals.